NOTARIAL DEEDS RELATED TO DEFAULTS, FRAUD AND EMBEZZLEMENT - Agung Iriantoro (Warmadewa Press, 2022)
The aim of this study is to find out the crime of fraud (Article 378 of the Criminal Code) and the criminal act of embezzlement (Article 372 of the Criminal Code) can be charged to one of the parties in the agreement made by the notarial deed is considered to have committed default. This study uses normative juridical methods, which means that this study focuses on favourable laws such as Law No. 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notary, the Civil Code, the Criminal Code, and other laws and regulations. Based on analysis, the results of this study revealed that if one of the parties in the agreement made by his notarial deed is considered to have committed a default, it cannot be charged with the crime of fraud (Article 378 of the Criminal Code) and the criminal act of embezzlement (Article 372 of the Criminal Code) based on Article 11 of Law No. 12 of 2005 concerning ratification of the International Covenant on Civil and Political Rights. Some judges' decisions with loose verdicts (slag van all rechttsvervolging), i.e., the act charged is proven, but the act of default does not constitute a criminal offence.